Assessment of threats to ecosystems in South America - Jarvis, Andy; Touval, Jerome L.; Castro, M.; Sotomayor L; Hyman, Glenn G. (Elsevier, 2010)
South America is blessed with both world-leading levels of biodiversity, and world-record breaking levels of habitat conversion in some areas. Under this highly dynamic context, sound conservation planning is needed and one component of effectively prioritising conservation interventions is through the assessment of threats to natural ecosystems. Here we present a continent-wide and spatially explicit threats assessment to natural ecosystems. A conceptual framework is presented which quantifies threat as a function of both the magnitude of the impacts of specific damaging human activities, and the variable response of different ecosystems to those impacts. The framework is then applied on seven different threat layers (accessibility, conversion to agriculture, fires, grazing pressure, infrastructure, oil and gas, recent conversion) to map out and spatially quantify the level of threat expected over the coming 2–5 year period. An aggregate threat layer is calculated, and the threats to major habitat types are evaluated. Tropical and Subtropical Grasslands, Savannas and Shrublands and Flooded Grasslands and Savannas are found to be under the greatest threat (0.36 and 0.35 aggregate threat respectively), both threatened most by fires (0.96), the former by accessibility (0.72) and the latter by grazing pressure (0.62). Tropical and Subtropical Moist Broadleaf Forests are the least threatened of all ecosystems (0.13), closely followed by Montane Grasslands and Shrublands (0.14). Overall, accessibility is shown to be a major issue across much of the continent, and fires are a significant threat in some identified regions. The results are being used by The Nature Conservancy to target conservation efforts in the region, and also to drive policies for threat abatement. Furthermore, the conceptual framework and methodology is applicable to any region and presents a useful means of prioritising conservation interventions across broad geographic regions.